Determinants of Timely Postnatal Care Utilization in Bagmati Province, Nepal: Evidence from NDHS 2022 - Devkota, Govinda Prasad; Devkota, Bijaya Mani; Khanal, Tantrika Raj (Journal of Tikapur Multiple Campus, 2026)
Postnatal care (PNC) provided soon after childbirth is vital for preventing illness and death among mothers and newborns. However, the use of PNC services in Nepal remains inadequate and unevenly distributed across different socio-demographic groups. This study sought to assess the extent of timely PNC utilization and to identify its key socio-demographic determinants among women in Bagmati Province, Nepal. The study analyzed secondary data from the 2022 Nepal Demographic and Health Survey (NDHS), including 468 women who had experienced a recent live birth. Patterns of PNC use were examined using descriptive statistics, while multivariate logistic regression analysis was applied to explore associations between timely PNC uptake and factors such as maternal age, birth order, educational attainment, household wealth, caste/ethnicity, religion, and place of residence. The findings reveal that maternal age, economic status, and birth order play a significant role in determining timely PNC utilization. Women aged 30 years and older were considerably more likely to receive postnatal care compared with younger women, hereas women with three or more children showed lower levels of PNC use. Household wealth emerged as the most influential factor, with women from the richest households demonstrating markedly higher utilization than those from poorer backgrounds. Substantial inequalities were also evident across caste and ethnic groups, particularly among Terai caste/ethnic women, who had the lowest likelihood of accessing PNC services. Overall, the study highlights that economic disadvantage, caste and ethnic marginalization, and higher parity remain critical obstacles to equitable postnatal care utilization in Nepal. Addressing these challenges requires targeted policy actions, culturally responsive interventions, financial assistance for disadvantaged households, and stronger involvement of rural institutions and community leaders to ensure timely and equitable access to PNC services.